ANALISIS ATRIBUT PRODUK TERHADAP KEPUTUSAN PEMBELIAN KARTU CELLULAR XL DI KOTA BANDUNG - Agus Rahmat Hermawanto; Asep Dadang (Gapenas Publisher, 2021)
From year to year, consumers of cellular operators, especially Global System for Mobiles operators, are increasing. One of the largest telecommunications companies in Indonesia is the open XL Axiata Limited Company. XL Axiata limited company is open. must maintain its performance. With the formation of competitive product attributes provide guidance, assurance, strength, confidence, and expectations to customers that they will be satisfied. The purpose of this research is to find out what attributes can influence purchasing behavior, so it can be seen which attributes are appropriate or not in accordance with the needs and desires of consumers where then the company can develop and perfect its products to better satisfy consumers and company goals in order to be reached